PENYULUHAN PENCEGAHAN STUNTING OLEH MAHASISWA KKN KOLABORATIF JEMBER DI DESA CAKRU, KECAMATAN KENCONG, KABUPATEN JEMBER - Paramitha, Nasywa Natania; Sanjaya, Adi Putra; Galini, Jauhairina; Syahdafi, Teuku M. Indra; Rofiki, Ainur; Umami, M. Mifthakul; Qodri, Moh Alil; Anggraini, Desta Rezzy; Rosadi, Imron; Muttaqiin, Ahyar; Az-Zahra, Fatima; Maulana, Raden M. Yusron; Insani, Shafalul Arnestya Nur; Zaharani, Zhafira; yasin, Mohammad Zeqi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Stunting is a situation where a child's height is shorter than that of his age. Based on data for 2020, WHO noted that children under the age of five experienced stunting by 21.3%. One of the areas with a fairly high stunting rate in the Jember area is Cakru Village, which is located in Kencong District. The stunting rate in this area reaches 50 out of a total of 503 children in the village. In this regard, the 002 Cakru Village Collaborative Community Service Group took the initiative to develop a work program aimed at reducing stunting rates in Cakru Village, Kencong District. The method used in this study was counseling on stunting prevention at the research location, namely Cakru Village, Kencong, Jember. Respondents in this counseling consisted of 40 mothers under five from Cakru Village, Kencong, Jember where in each hamlet there were 10 participants from Krajan Hamlet, Igir-Igir Hamlet, Tempuran Hamlet, and Gondangrejo Hamlet. The age of the children who were targeted in the data collection was children in the first 1,000 days of birth. The socialization of Stunting Prevention Counseling in Cakru Village, Kencong District, was carried out well. All residents participated in this program enthusiastically, by participating in counseling and answering quizzes (questions and answers) well and understanding the contents of the material.